Changes in microbiotic enzyme activity on soil organic matter decomposition, on an altitudinal gradient of the volcano Iliniza Ecuador, as a model for climate change impacts on carbon storage in Andean peatlands - Brück, Stefan Alexander (2023)
The Andean Paramo unites distinct environments characterized as neotropical mountain ecosystems lying at high elevations between the tree line and the rocky zone of the Andean Mountain chain from 2900 up to 5000 m. It bears the highest average diversification rate among all biodiversity hotspots on earth. Its role as a carbon sink and its astonishing water retention capacity play critical roles in the interaction with Andean downslope ecosystems. Chapter 1 reviews how low organic matter degradation leads to the massive accumulation of peat-like carbon deposits and how this carbon sink might turn into a carbon source in the future due to climatic change, supported by research evidence of northern hemisphere peatlands. Chapter 2 treats the isolation of filamentous fungal strains from remote habitats with extreme climatic conditions in the paramo, discovering several enzymes with attractive properties, useful in various industrial applications. Among these, cold-adapted enzymes from fungi with psychrotrophic behavior are valuable agents in industrial processes aiming to reduce energy. Out of eight strains isolated from the soil of the paramo highlands of Ecuador, three were selected for further experimentation and identified as Cladosporium michoacanense, Cladosporium sp. (cladosporioides complex), and Didymella sp. The secretion of seven enzymes, endoglucanase, exoglycanase, β-D-glucosidase, endo-1,4-βxylanase, β-D-xylosidase, acid, and alkaline phosphatases, were analyzed under agitation and static conditions optimized for the growth period and incubation temperature. Cladosporium strains under agitation and incubation for 72 h mostly showed substantial activation for endoglucanase up to 4563 mU/mL and xylanase up to 3036 mU/mL. Meanwhile, other enzymatic levels varied depending on growth and temperature. Didymella sp. showed the most robust activation at 8 °C, indicating an interesting profile for applications in bioremediation and wastewater treatment processes in cold climates. Chapter 3 describes the changing activity of sulfatase (Sulf), phosphatase (Phos), n-acetyl-glucosaminidase (N-Ac), cellobiohydrolase (Cellobio), β-glucosidase (β-Glu), and peroxidase (POX) on an altitudinal scale from 3600-4200 m, in rainy and dry seasons at 10 and 30 cm sampling depth, related to physical and chemical soil characteristics, like metals and organic elements. Linear fixedeffect models were established to analyze these environmental factors to determine distinct decomposition patterns within paramo soils. The data suggests a strong tendency toward decreasing enzyme activities at higher altitudes and in the dry season up to two-fold stronger activation for Sulf, Phos, Cellobio, and β-Glu. Especially the lowest altitude showed considerably stronger N-Ac, β-Glu, and POX activity. Sampling depth revealed significant differences for all hydrolases but Cellobio, but it had minor effects on model outcomes. Further organic rather than physical or metal components of the soil explain the enzyme activity variations. Although the levels of phenols coincided mostly with the soil organic carbon content, there was no direct relation between hydrolases, POX activity, and phenolic substances. The outcome suggests that slight environmental changes with global warming might cause important changes in enzyme activities leading to increased organic matter decomposition at the borderline between the paramo region and downslope ecosystems. In chapter 4 we assumed that low decomposing activity is directly linked to its microbial composition, which has not yet been studied in detail in paramo soil. 16S- for archaea and bacteria and ITS-sequences for fungi were amplified for analysis on 4 distinct altitudes marking vegetational zones in the dry and rainy seasons. Samples were taken in triplicate and pooled. Taxonomical data of richness and abundance revealed that bacterial communities variate stronger with the season than with altitudinal effects. The most abundant phyla were Acidobacteriota, Actinobacteriota and Bacteriodota. Proteobacteriota, commonly described as the leading soil phylum, only showed little abundance. Fungi, on the other hand, showed greater variation in diversity for altitudinal and seasonal effects. Ascomycota, Basidiomycota, and Mortierellomycota were most abundant. In comparison to enzyme activity of chapter 3, the global pattern of fungal diversity could explain to a greater extent the observed differences in the decomposition of organic matter. The distribution of fungal classes indicates unique patterns for the paramo environment, which invites further investigation.